Modern religions & successful change - Tanner, R. E. S. (Ralph E. S.), 1921- (Delhi : Manak Publications, 2005)
Study with reference to Asia, Africa, and Europe
Includes bibliographical references (p. [305]-320) and index
Keywords: Religion and sociology -- Asia; Religion and sociology -- Africa; Religion and sociology -- Europe; Asia -- Religious life and customs; Africa -- Religious life and customs; Europe -- Religious life and customs